MATCHNOTE!, APLIKASI ANDROID PENCATATAN PERTANDINGAN OLAHRAGA SEPAK BOLA DAN FUTSAL - , AGA SETYO PURNOMO, Arif Nurwidyantoro, S.Kom., M.Cs. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Recording the statistic data of football and futsal match mostly conducted manually by using the recording board. Over the times, the needs for mobile recording media are increasing. This is supported by the increasing number of mobile device. MatchNote! application is built according to the necessity of footballer, coach, match organizer, in recording all events during the match. This application is easily accessed by android smartphone minimum version 2.3 (Gingerbread). MatchNote! Application is built by using java programing language and SQLite database. This application could record the match score, goal scorer, match faults, and players substitution. All of the data can be stored and shared into the social networks as image.